Local Density and Foreign Subsidiary Performance - Miller, Stewart R.; Eden, Lorraine (Academy of Management Journal, 2006)
Local density (the number of firms vying for similar resources in a local environment) has been overlooked in explaining foreign subsidiary performance. This study drew upon the concepts of liability of foreignness and density dependence to examine how local density within a host country affected performance—directly and indirectly— through effects on market experience and strategic conformity. We found that local density was negatively related to foreign subsidiary performance and that market experience was less beneficial in high-density environments. Strategic conformity enhanced performance in low-density environments but adversely affected performance in high-density environments.